Collagen/pristine graphene as an electroconductive interface material for neuronal medical device applications. (December 2022) - Maughan, Jack; Gouveia, Pedro J.; Gonzalez, Javier Gutierrez; Leahy, Liam M.; Woods, Ian; O'Connor, Cian; McGuire, Tara; Garcia, James R.; O' Shea, Donagh G.; McComish, Sarah F.; Kennedy, Oran D.; Caldwell, Maeve A.; et al.
Highlights: Graphene/collagen (CpG) composite was produced with high conductivity and neurocompatibility. CpG composite was used to deliver effective electrical stimulation to neuronal cells. CpG composite processed into different neural-interfacing devices by dry casting, freeze-drying, and 3D printing. Abstract: The growing clinical demand for electrical stimulation-based therapies requires the development of novel conductive biomaterials that balance conductivity, biocompatibility, and mechanical performance. Traditional conductive materials often induce scarring, due to their stiffness and poor biocompatibility, presenting challenges to their clinical translation. To address these issues, we report the development of an electroconductive pristine graphene-based (pG) composite material for central nervous system applications, consisting of type I collagen loaded with 60 wt% pG to yield conductivities (∼1.5 S/m) necessary for efficient electrical stimulation. Neurons and glial cells grown on composite films exhibited robust growth, and glial cells exhibited no change in inflammatory markers. Electrical stimulation of primary neurons on the composite enhanced neurite outgrowth, cellular viability and morphology compared to collagen controls. Finally, we demonstrated the versatility and potential applications of the composite material for neuronal medical device applications by fabricating a range of conductive, neural-interfacing structures, including porous scaffolds, microneedle arrays, and 3D-printed circuits for bioelectronics. These results show that CpG composites form a versatile neurotrophic platform that balances biocompatibility and physiologically relevant conductivity with robust mechanical properties that allow for the production of a range of next-generation neuroprosthetic devices. Graphical abstract: Image, graphical abstract Pristine graphene (pG) suspensions were obtained through liquid-phase exfoliation via sonication from graphite in gelatin solution. Collagen/pG composites were fabricated to create films and microneedle arrays by dry casting, 3D porous structures through freeze drying, and bioelectronic circuits through 3D printing. Material properties can be tuned by changing collagen concentration and loading of pG. The composites trophically supported the growth of several different neural cell types and facilitated electrical stimulation of cortical neurons to enhance their growth. Together, these results demonstrate the versatility of CpG composites as a platform that balances biocompatibility and physiologically relevant conductivity with robust mechanical properties that allow for the fabrication of a range of next-generation medical devices for neural applications.